2007
DOI: 10.1016/j.physa.2007.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Particle–wall collision statistics in the open circular billiard

Abstract: In the open circular billiard particles are placed initially with a uniform distribution in their positions inside a planar circular vesicle. They all have velocities of the same magnitude, whose initial directions are also uniformly distributed. No particle-particle interactions are included, only specular elastic collisions of the particles with the wall of the vesicle. The particles may escape through an aperture with an angle 2δ. The collisions of the particles with the wall are characterized by the angula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The initial momenta of all particles are assumed to be equal p 0 . Classical dynamics of unperturbed open billiards has been extensively studied both for integrable and chaotic geometries [24]- [30]. In particular, it was found in the Refs.…”
Section: Kicked Billiard Vs Kicked Rotormentioning
confidence: 99%
See 1 more Smart Citation
“…The initial momenta of all particles are assumed to be equal p 0 . Classical dynamics of unperturbed open billiards has been extensively studied both for integrable and chaotic geometries [24]- [30]. In particular, it was found in the Refs.…”
Section: Kicked Billiard Vs Kicked Rotormentioning
confidence: 99%
“…We note that classical dynamics of unperturbed open billiards have been studied for integrable and chaotic geometries by many authors (see, e.g., Refs. [24]- [30]). In particular, it was found that the number of (non-interacting) particles in nonintegrable open billiard decreases exponentially, while in case of regular billiard it decreases according to power law [24]- [26].…”
Section: Introductionmentioning
confidence: 99%